Emergence and control of an outbreak of infections due to Panton‐Valentine leukocidin positive, ST22 methicillin‐resistant Staphylococcus aureus in a neonatal intensive care unit. (20th August 2012) - Pinto, A. N.; Seth, R.; Zhou, F.; Tallon, J; Dempsey, K.; Tracy, M.; Gilbert, G. L.; O'Sullivan, M. V. N.
Abstract Methicillin resistant Staphylococcus aureus (MRSA) infection can cause significant morbidity and mortality in neonates. We investigated a nosocomial MRSA outbreak in a neonatal intensive care unit (NICU), using a novel typing method. Following two fatal cases, in May 2011, a prospective outbreak investigation was conducted, involving neonates, mothers and healthcare workers in a large tertiary NICU in Sydney. MRSA isolates were characterized by antimicrobial susceptibility testing, a multiplex PCR‐based reverse line blot (mPCR/RLB) binary typing system and other molecular typing methods. Over 7 months, 14 neonates were colonized with MRSA and six infected: three with superficial lesions and three with life‐threatening disease, including the two index cases, who died despite empirical treatment with vancomycin. Isolates from 15 neonates were indistinguishable by RLB typing and identified as a PVL‐producing ST22 SCCmec IV MRSA strain, which was resistant to gentamicin and trimethoprim‐sulphamethoxazole. The outbreak strain was also isolated from one healthcare worker, one environmental swab and one father, but the source remained obscure. During the same period several different non‐multiresistant and multiresistant MRSA strains were isolated from five neonates, five mothers (including two whose infants were colonized with the outbreak strain), one father, three healthcare workers and two environmental swabs. Rapid turnaround time of typing results allowed us to recognize and define the outbreak and implement targeted infection control interventions. PVL‐producing ST22 SCCmec IV MRSA appears to be a virulent and highly transmissible pathogen in the NICU, which was difficult to control.